2001
DOI: 10.1021/jf010163m
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Determination, and Biological Evaluation of a Novel Styrene Trimer Contained in Polystyrene Food Containers. 2

Abstract: An unidentified styrene trimer (ST) isolated from the acetonitrile extract of polystyrene (PS) food containers was characterized as (1S*,6R*,7S*,8S*,11R*)-6,11-diphenyltricyclo[6,2,2,0(2,7)]dodeca-2,9-diene. The content and migration of this compound in PS food containers were determined by GC-MS (SIM). Furthermore, an endocrine-disrupting effect was tested using in vitro and in vivo assays of the compound. In conclusion, it seems that the compound does not present the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…28,46 In one of the few works with experimental evidence, Hirano et al identified a styrene trimer (1,3,5-triphenylcyclohexane) in the extracts of PS food packaging. 56 After both in vitro and in vivo tests this oligomer showed no endocrine-disrupting effect.…”
Section: Toxicological Considerationsmentioning
confidence: 94%
See 1 more Smart Citation
“…28,46 In one of the few works with experimental evidence, Hirano et al identified a styrene trimer (1,3,5-triphenylcyclohexane) in the extracts of PS food packaging. 56 After both in vitro and in vivo tests this oligomer showed no endocrine-disrupting effect.…”
Section: Toxicological Considerationsmentioning
confidence: 94%
“…No evidence of genotoxicity or endocrine disruption was found. Nakai and co-workers also came to the conclusion that the risk of genotoxicity due to the consumption of the styrene oligomers that migrated from PS packaging into the food is very low. , In one of the few works with experimental evidence, Hirano et al identified a styrene trimer (1,3,5-triphenylcyclohexane) in the extracts of PS food packaging . After both in vitro and in vivo tests this oligomer showed no endocrine-disrupting effect.…”
Section: Pes and Ps Oligomersmentioning
confidence: 99%
“…When using food simulants (Table 2), in some cases n-heptane was used (Hirano et al 2001;Kaneko et al 1999;Kawamura et al 1998aKawamura et al , 1998bYamada et al 2000a), which is not a food simulant according to Commission Regulation (EU) No 10/2011 and thus might not lead to results comparable to real food. Furthermore, the measured content of the SD and ST in food simulants is quite high when typical simulants for fatty food are used.…”
Section: Contents Of So In Fcm and Migration Into Food/food Simulantsmentioning
confidence: 99%
“…2 Studies have been reported on the presence of styrene monomers, trimers, and oligomers in the leachates of waste dump yards. [3][4][5] In addition, the presence of styrene in water bodies, industrial effluents, and soil has been reported in the literature. 6,7 Detailed studies on the harmful effects of styrene, toluene, phenol, and formaldehyde on the environment have also been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%